P200 A review of domiciliary non-invasive ventilation for patients with motor neurone disease (MND) in a regional centre. (December 2018) - Thompson, F; Harbord, P; Ewles, S; Cull, F; Gibson, D; Sivaloganathan, A; Dushianthan, A; Wilkinson, J
Abstract : Introduction and objectives: Our Respiratory Centre providea regional (Hampshire and Dorset) domiciliary non-invasive ventilation (NIV) service for around 300 patients with chronic respiratory insufficiency. This includes a number of patients with motor neurone disease (MND). Poor respiratory muscle function and bulbar symptoms at diagnosis of MND are associated with poor prognosis. 1 NICE guidance suggests consideration of NIV for MND patients, who have PaCO2 of >6 kPa or symptoms of hypoventilation, including those with severe bulbar involvement. 2 The aim of this study is to review our current NIV practices in this patient cohort. Method: All patients with MND who are on domiciliary NIV were identified. Data were collected from all available electronic sources. Several clinical parameters were recorded, including tolerability, continued use of NIV, hospitalisations and blood gas analysis for patients with and without primary bulbar symptoms. Statistical comparison between groups was not performed due to low patient numbers. Results: 34 patients were identified (23 male; 11 female with a mean age of 64.8 years). Overall, 22 patients (65%) had electively planned NIV set-up. Patients with bulbar symptoms had lower PaCO2 and HCO3 - levels at NIV initiation compared to the patients without bulbar symptoms. Initial forced vital capacity (FVC) was higher in the cohort with bulbar symptoms. NIV usage was similar between these two groups. Discontinuation due to intolerance was only noticeable in the bulbar group. NIV related hospital admissions were a rareoccurrence for both groups. Conclusions: MND patients account for about 10% of our domiciliary NIV cohort and among those a third had emergency set-up during an acute admission. This highlights the importance of early identification of patients with respiratory muscle weakness to prevent acute hospitalisations with ventilatory failure. NIV is relatively well tolerated by both MND groups with and without bulbar symptoms. References: Stambler N, Charatan M, Cedarbaum JM. ALS CNTF Treatment Study Group Prognostic indicators of survival in ALS. Neurology1998;50:66–72. NICE. Motor neurone disease: assessment and management 2016. Available at: https://www.nice.org.uk/guidance/NG42